Development of remote monitoring system for biomedical equipment - Macedo, Felipe Soares (2017)
Introduction: Videolaparoscopy is an effective technique to access the body cavities. This technique maintains a minimal invasive impact in relation to other surgical procedures. However, in order to accomplish this technique it is necessary to have trained health professionals and an appropriate, robust set of equipment. The objective of this article is to present and describe a remote monitoring system which was developed to monitor and assistance precision biomedical equipment, such as the ones used for videolaparoscopy. This monitoring system, VERA, implements a collaborative methodology between health professionals and equipment maintenance professionals. The system was designed using the 3C model to provide the collaborative characteristics. Moreover, the development and implementation used web technologies. Throughout this process, modeling of the VERA system included conceptual and technical methods such as wireframes, site map and user interaction modeling. The VERA system allowed a collaborative work environment for the technical assistance team (for maintenance purposes) and the health professional responsible for the videolaparoscopy. The steps developed so far reveal that the system developed through the 3C model contributes to the creation of a collaborative environment in the remote monitoring of videolaparoscopic medical equipment. This, in turn, allows the technical assistance team to carry out diagnostic and maintenance with celerity, making it possible to ensure precise and efficient procedures in the Brazilian Unified Health System.